Cool food : erasing your carbon footprint one bite at a time - Downey, Robert, Jr., 1965-; Kostigen, Thomas (Blackstone Publishing, 2024)
"What we eat matters--to us, and to the planet. Cool food is a game-changing new food category and way of thinking that can help fix the climate. This ... book will show you how to make simple choices, starting today--in the supermarket, in your kitchen, and in the world--to reduce your environmental impact. Hundreds of cool foods exist, but until now have gone largely uncelebrated for their climate-positive powers. Some of these foods may already be on your shelf, and some are just on the horizon. But cool food is much more than just a shopping list: it's a way of life vitally important to our future. Packed with eye-opening information, actionable items, and two dozen ... recipes, Cool Food comes alive with ... storytelling and refreshing humor"--